Combating Cybercrimes in Federal University Digital Libraries in Nigeria - M.O., Okoye; N.E., Osadebe (Journal of Home Economics Research, 2024)
This study was focused on cybercrimes existing in Federal University Digital Libraries. Questionnaire was used for data collection from 120 librarians working in Federal University Digital Libraries in Nigeria. A survey research design was used for the study. The population of the study was made up of 120 librarians. Mean and percentages were used for data analysis. The major findings include that internet pornography and scam mails were the greatest cybercrimes committed in Federal University Libraries. It also identified major stakeholders in the control of cybercrimes as staff in charge of the computer systems. .It was further revealed that non- coverage of cybercrimes under library laws and regulations constituted critical challenge to the control of cybercrimes. The study recommended among others, the need to entrench stiff penalties against cybercrimes in University laws and regulations so as to instill discipline and sustain relevance of cybercafés in enhancing academic excellence.